Atomically Precise Water-Soluble Gold Nanoclusters: Synthesis and Biomedical Application - Yan, Qian; Yuan, Zhaotong; Wu, Yating; Zhou, Chunmei; Dai, Yihu; Wan, Xiaoyue; Yang, Dan; Liu, Xu; Xue, Nianhua; Zhu, Yan; Yang, Yanhui (Precision Chemistry, 2023)
Atomically precise water-soluble gold nanoclusters (Au NCs) protected by organic ligands have attracted growing attention in serving as unique nanomaterials with the potential to generate theranostic tools (bioimaging, biosensing, and biotherapy), due to their ultrasmall size, superior photoluminescence, good biocompatibility, and nontoxicity. More importantly, Au NCs afford a well-defined atomic packing structure and molecular purity, providing a superior platform to unravel the structure–performance correlations for biodistribution, biological pharmacokinetics, and excretion of Au NCs. In this Review, we mainly survey the synthesis of water-soluble Au NCs and the recent progress in biomedicine of Au NCs, including bioimaging, biosensing, and biotherapy. The effects of ligand and size on the biomedical properties are discussed in detail. We hope that the advances in this research area can expand the applications of Au NCs in biomedicine.